2002
DOI: 10.1111/1540-627x.00059
|View full text |Cite
|
Sign up to set email alerts
|

The Ethical Outlook of Micro Business Operators

Abstract: This paper reports the findings of an investigation into the ethical outlook of micro business operators. The study was conducted in Australia and is the first such examination of ethical perspectives in this segment of the business population. Micro business is internationally recognizable, economically significant, and strongly entrepreneurial, and it has a high level of control over the values it enacts. The study indicates that ethical considerations are important to Australian micro business operators. Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
1
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 7 publications
3
29
1
3
Order By: Relevance
“…Second, our study underscores the importance of the moral autonomy of small-business owner-managers. Whereas previous studies have emphasized the important role of owner-managers and their personal values in ethical business decision-making (e.g., Dawson et al, 2002;Spence and Rutherfoord, 2001;Quinn, 1997), our results indicate how managers' perceptions regarding their business decisions are emotionally embedded. We therefore suggest that socially and culturally constructed emotions provide a fruitful context in which to understand the limitations of owner-manager personal and moral autonomy.…”
Section: Introductioncontrasting
confidence: 98%
“…Second, our study underscores the importance of the moral autonomy of small-business owner-managers. Whereas previous studies have emphasized the important role of owner-managers and their personal values in ethical business decision-making (e.g., Dawson et al, 2002;Spence and Rutherfoord, 2001;Quinn, 1997), our results indicate how managers' perceptions regarding their business decisions are emotionally embedded. We therefore suggest that socially and culturally constructed emotions provide a fruitful context in which to understand the limitations of owner-manager personal and moral autonomy.…”
Section: Introductioncontrasting
confidence: 98%
“…A study conducted by Dawson, Breen and Satyen (2002) found that ethical concerns are significant to Australian small business operators, although some variation occurs according to age, gender and education. Findings from earlier research conducted overseas report significant differences in owner/managers' attitudes towards environmental issues (Rutherfoord, Blackburn & Spence 2000) and in their values towards their community (Miller & Besser 2000;Besser 1999).…”
Section: Small Business and Sustainabilitymentioning
confidence: 99%
“…Así por ejemplo, se ha podido contrastar que el hecho de ser mujer, poseer unos mayores principios morales y religiosos o creer que todo lo que uno hace tiene su posterior recompensa son significativos de una mayor ética (Brown y King, 1982;Au y Tse, 2001); y que el egoísmo o la importancia otorgada al dinero inciden negativamente sobre el nivel ético (Au y Tse, 2001). Se debe señalar que algunos trabajos empíricos encontraron también una relación positiva entre la edad y el comportamiento ético (Posner y Schmidt, 1984;Barnett y Karson, 1987;Serwinek, 1992;Smith y Oakley, 1994;Dawson et al, 2002).…”
Section: Relaciones Factores-prácticas-efectosunclassified
“…De este modo, contrastaron que mientras que los individuos con mayor nivel de estudios reglados eran más proclives a participar como líderes de organizaciones de carácter social y local, aquellos que ostentaban mayores recursos tendían a ofrecer un tipo de ayuda financiera y técnica, siendo esto último aun más probable en aquellas situaciones en las que la empresa se encontraba en un entorno vulnerable desde una perspectiva económica. La influencia que la edad y la educación tienen sobre la actitud, fue del mismo modo analizada por Dawson et al (2002) para el caso de propietarios de microempresas australianas, comprobándose que los mismos otorgaban una mayor importancia al comportamiento ético en su actividad diaria a medida que aumentaba tanto la edad como el nivel de estudios.…”
Section: Relaciones Factores-prácticas-efectosunclassified